An Operational Process for Workforce Planning - Emmerichs, Robert M. (RAND Corporation, 2004)
Workforce planning is an activity intended to ensure that investment in human capital results in the timely capability to effectively carry out an organization's strategic intent. This report examines the purposes of workforce planning, identifies key factors contributing to successful workforce planning, and describes a RAND-developed process for conducting workforce planning.